2016
DOI: 10.1016/j.materresbull.2016.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and properties of crystalline and nanocrystalline MnPS 3 -poly(phenylene vinylene) intercalates

Abstract: The preparation of luminescent semiconducting nanocomposites of crystalline and amorphous manganese phosphorus trisulfide (MnPS 3 ), containing intercalated poly(phenylene vinylene) [PPV] is reported. The materials were characterized by thermogravimetric analysis, infrared and Raman spectroscopy and X-ray diffractometry. Scanning electron microscopy was used to monitor the crystallinity and morphology of the host materials.An average increase of 5.05 Å in the interlayer distance of MnPS 3 was observed by XRD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…. X8 are observed, in fair agreement with previously reported observations of the specific phonon modes in MnPS 3 crystals 4, [16][17][18][19] . The temperature evolution of all but the X1 and X2 peaks is rather smooth.…”
Section: Resultssupporting
confidence: 92%
“…. X8 are observed, in fair agreement with previously reported observations of the specific phonon modes in MnPS 3 crystals 4, [16][17][18][19] . The temperature evolution of all but the X1 and X2 peaks is rather smooth.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, Raman spectroscopy as a fast and nondestructive characterization technique, has been extensively used to study the lattice structural, interlayer coupling, and phase transition temperature of 2D materials . In principle, the onset of magnetic ordering lowers the crystal symmetry, resulting in variation of the Raman intensity and frequency, as well as possible activation of new Raman modes. For example, the Néel temperature related to the magnetic phase transition of NiPS 3 and FePS 3 has successfully been revealed by the temperature-dependent Raman measurements. , Although several Raman studies on MnPS 3 have been reported, most researchers have focused on bulk materials and intercalation compounds. , More significantly, identification of the Raman model is not rigorous enough, , and temperature-dependent Raman studies on magnetic ordering of few-layer MnPS 3 , are still lacking so far.…”
mentioning
confidence: 99%
“…20,23 Although several Raman studies on MnPS 3 have been reported, most researchers have focused on bulk materials 24 and intercalation compounds. 25,26 More significantly, identification of the Raman model is not rigorous enough, 24,26 and temperature-dependent Raman studies on magnetic ordering of few-layer MnPS 3 27,28 are still lacking so far.…”
mentioning
confidence: 99%
“…For instance, it was reported that there is a strong tendency in MnPS 3 and FePS 3 for cation exchange, along with the creation of M 2+ vacancies during intercalation. 15,16,19–21 In contrast, no direct intercalation of pyridine was observed for NiPS 3 , although metal-to-ligand interaction would be of a similar bond strength. 22 Pattayil et al suggested that a possible reason for this is the difference in the crystal field energy, which stabilizes Ni in the crystal structure, 22 thereby impeding the pyridine intercalation.…”
Section: Introductionmentioning
confidence: 96%
“…For example, insertion of complex ammonium cations with different organic groups such as tetrabutyl ammonium (TBA + ), tetrapropyl ammonium (TPA + ) and cetyltrimethyl ammonium (CTA + ) were demonstrated in NiPS 3 , 13,14 while MnPS 3 is known to be a host for poly(phenylene vinylene) and for pyridine. 15,16…”
Section: Introductionmentioning
confidence: 99%